Valuing complex natural resource systems the case of the Lagoon of Venice - Alberini, Anna.; Rosato, Paolo, 1958-; Turvani, Margherita; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2006)
In complex natural resource systems, modifications or disruptions tend to affect many and diverse components of the ecological system, settlements and groups of people. This book uses the Lagoon of Venice-- a unique natural resource, wildlife habitat, centre of cultural heritage and recreational site-- as an example of one such system that has been heavily affected by human activities, including the harvesting of natural resources and industrial production. The contributors explore the Lagoon's potential for regeneration, examining public policies currently under consideration. The aim of these policies is to restore island coastlines and marshes, fish stocks, habitat and environmental quality, defend morphology and landscape through the strict control of fishing practices, and to protect the islands from high tides.
pt. 1. Non-market valuation methods -- pt. 2. Applications of non-market valuation methods in the lagoon of Venice -- pt. 3. Assessing remediation options and policies for contaminated sites in the Venice area.
Includes bibliographical references and index.
Keywords: Natural resources -- Valuation -- Italy -- Venice, Lagoon of; Environmental policy -- Italy -- Venice, Lagoon of; Venice, Lagoon of (Italy) -- Environmental conditions; Lagoon ecology -- Italy -- Venice, Lagoon of; Electronic books